I‐125 ROPES eye plaque dosimetry: Validation of a commercial 3D ophthalmic brachytherapy treatment planning system and independent dose calculation software with GafChromic® EBT3 films. Issue 12 (12th November 2013) - Poder, Joel; Corde, Stéphanie
Abstract : Purpose: : The purpose of this study was to measure the dose distributions for different Radiation Oncology Physics and Engineering Services, Australia (ROPES) type eye plaques loaded with I‐125 (model 6711) seeds using GafChromic ® EBT3 films, in order to verify the dose distributions in the Plaque Simulator™ (PS) ophthalmic 3D treatment planning system. The brachytherapy module of RADCALC ® was used to independently check the dose distributions calculated by PS. Correction factors were derived from the measured data to be used in PS to account for the effect of the stainless steel ROPES plaque backing on the 3D dose distribution. Methods: : Using GafChromic ® EBT3 films inserted in a specially designed Solid Water™ eye ball phantom, dose distributions were measured three‐dimensionally both along and perpendicular to I‐125 (model 6711) loaded ROPES eye plaqueˈs central axis (CAX) with 2 mm depth increments. Each measurement was performed in full scatter conditions both with and without the stainless steel plaque backing attached to the eye plaque, to assess its effect on the dose distributions. Results were compared to the dose distributions calculated by Plaque Simulator™ and checked independently with RADCALC ® . Results: : The EBT3 film measurements without the stainless steel backing were found to agree with PS and RADCALC ® to within 2% and 4%, respectively, on the plaque CAX. Also, RADCALC ® was found to agree with PS to within 2%. The CAX depth doses measured using EBT3 film with the stainless steel backing were observed to result in a 4% decrease relative to when the backing was not present. Within experimental uncertainty, the 4% decrease was found to be constant with depth and independent of plaque size. Using a constant dose correction factor of T = 0.96 in PS, where the calculated dose for the full water scattering medium is reduced by 4% in every voxel in the dose grid, the effect of the plaque backing was accurately modeled in the planning system. Off‐axis profiles were also modeled in PS by taking into account the three‐dimensional model of the plaque backing. Conclusions: : The doses calculated by PS and RADCALC ® for uniformly loaded ROPES plaques in full and uniform scattering conditions were validated by the EBT3 film measurements. The stainless steel plaque backing was observed to decrease the measured dose by 4%. Through the introduction of a scalar correction factor (0.96) in PS, the dose homogeneity effect of the stainless steel plaque backing was found to agree with the measured EBT3 film measurements.